2018
DOI: 10.1101/502781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spliceosomal Prp8 intein at the crossroads of protein and RNA splicing

Abstract: protein splicing 15 16 * Corresponding authors: Marlene Belfort (mbelfort@albany.edu) or Hongmin Li 17 (hongmin.li@health.ny.gov) 18 ABSTRACT 19The spliceosome is a large ribonucleoprotein complex that removes introns from 20 pre-mRNAs. At its functional core lies the essential Prp8 protein. Across diverse 21 eukaryotes, this protein cofactor of RNA catalysis harbors a self-splicing element, called 22 an intein. Inteins in Prp8 are extremely pervasive and are found at seven different sites in 23 various specie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Divalent cations have been shown to influence protein splicing, in some cases binding directly to the intein ( 21 , 34 , 35 ). Further, it has been shown that DnaBi1 is subject to conditional splicing regulation via the redox state of catalytic cysteines ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Divalent cations have been shown to influence protein splicing, in some cases binding directly to the intein ( 21 , 34 , 35 ). Further, it has been shown that DnaBi1 is subject to conditional splicing regulation via the redox state of catalytic cysteines ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inteins are often found in experimentally challenging organisms such as pathogenic bacteria (e.g., M. tuberculosis ) ( 11 , 25 ), pathogenic fungi (e.g., Cryptococcus neoformans ) ( 21 , 35 ), and extremophilic archaea (e.g., Pyrococcus horikoshii ) ( 9 , 10 ). As a result, studies examining conditional protein splicing (CPS) in the native host have proven difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations